2009
DOI: 10.1038/oby.2009.159
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Obesity‐associated Loci Identified in Genome‐wide Association Studies in the Determination of Pediatric BMI

Abstract: The prevalence of obesity in children and adults in the United States has increased dramatically over the past decade. Besides environmental factors, genetic factors are known to play an important role in the pathogenesis of obesity. A number of genetic determinants of adult BMI have already been established through genome‐wide association (GWA) studies. In this study, we examined 25 single‐nucleotide polymorphisms (SNPs) corresponding to 13 previously reported genomic loci in 6,078 children with measures of B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

16
156
3
8

Year Published

2012
2012
2016
2016

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 167 publications
(183 citation statements)
references
References 19 publications
16
156
3
8
Order By: Relevance
“…In line with the results of the GWAS in a large pediatric cohort of European ancestry (Zhao et al, 2009), we have found a significant association between obesity, evaluated using BMI percentile (Cole et al, 2000), and one or two Met alleles of the BDNF Val66Met polymorphism. In our study obese children and adolescents were more likely to be carriers of the Met/Val genotype, the Met allele, and the combined Met/Met and Met/Val genotypes compared to normal weight groups.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…In line with the results of the GWAS in a large pediatric cohort of European ancestry (Zhao et al, 2009), we have found a significant association between obesity, evaluated using BMI percentile (Cole et al, 2000), and one or two Met alleles of the BDNF Val66Met polymorphism. In our study obese children and adolescents were more likely to be carriers of the Met/Val genotype, the Met allele, and the combined Met/Met and Met/Val genotypes compared to normal weight groups.…”
Section: Discussionsupporting
confidence: 85%
“…This speculation might be confirmed by the fact that weight gain, induced by antipsychotic drugs, is associated with BDNF serum levels in female schizophrenic patients, while carriers of the Met/Met genotype have lower BDNF levels than carriers of the Val allele (Zhang et al, 2008). Our finding of the significant association between BDNF Val66Met genotype and obesity in children and adolescents is supported by GWAS data, which found a significant association between BDNF Val66Met and obesity in children (Zhao et al, 2009) and adults (Croteau-Chonka et al, 2011;Speliotes et al, 2010).…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…The lack of association observed in the adolescent/young adult period for SH2B1 is supported by the published literature. Studies in European pediatric populations have also failed to find an association between SH2B1 and BMI or obesity (6,14,15). It is possible that SH2B1, a neuronal gene implicated in glucose homeostasis and leptin signaling (24,25), fails to play a measurable effect on BMI until other endogenous or exogenous factors that only manifest or accumulate later in life occur.…”
Section: Discussionmentioning
confidence: 97%
“…In the past 5 years, genome-wide association studies (GWASs) have identified over 30 common genetic loci associated with body mass index (BMI, kg/m 2 ) mainly in European adult samples, with an average age often greater than 50 (4 -10). Whereas several loci identified in adults have also been found to be associated with BMI in childhood (6,(11)(12)(13)(14)(15)(16)(17)(18)(19)(20) and two loci were recently identified in childhood obesity (17), little is known about these obesity susceptibility loci across high-risk periods for weight gain, such as adolescence and young adulthood. The influence of these loci in adolescence and young adulthood remains largely speculative from previously established association studies that illustrate the association of these loci on BMI during middle-aged adulthood and/or childhood.…”
Section: Introductionmentioning
confidence: 99%